Copiii străzii în București: o abordare nouă pentru studierea unei probleme perpetue - Groza, Victor; Ghindia, Dennis; Bibb, Lawrie; Shrader, Catherine; Loue, Sana; Krihwan, Ann Marie; Leto, Tim (Calitatea Vieții, 1999)
Without abstract